Archival information and organic information: a conceptual analysis of the Brazilian literature - Valentim, Marta Lígia Pomim [UNESP]; Lousada, Mariana [UNESP] (Epi, 2010)
Information has increasingly become a crucial resource for organizations that want to remain competitive in the market. For this reason, analysis and a correct understanding of informational types that are present in these environments become relevant to achieving the highest levels of performance. The aim of this paper is to review the literature of the concepts of organic and archival information within the organizational context/business environments. This is still an emerging theoretical field and therefore is conducive to intense discussions. We point out elements that help to characterize and distinguish these two types of information.
Keywords: Organic Information; Archivist information; Archivology; Information science; Epistemology